Lily Quench and the magicians' pyramid - Prior, Natalie Jane, 1963-; Dawson, Janine (New York : Puffin Books, 2003)
While Lily Quench and Queen Dragon pursue their mission to close the Eye Stones and battle a trio of magicians, Queen Evangeline and King Lionel attempt to apprehend a dangerous palace intruder.
9 13
Keywords: Dragons -- Fiction; Magicians -- Fiction; Fantasy